UPAYA DINAS TENAGA KERJA PROVINSI JAWA TENGAH DALAM MENGAWASI TENAGA KERJA ASING (Studi Kasus di Kota Semarang dan Kabupaten Demak) - Dalila, Mirza; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2018)
The growth and the development of era like nowadays make people workhard, in this case the local workers should have an adequate ability to compete with with expatriates. The expatriates who work in Indonesia should be under supervision. The office which has responsibility and authority to supervise expatriates is the Manpower and Transmigration office, and particular to this research is the Manpower and Transmigration Office of Central Java. The supervision is done to protect local workers and the regulations used in Supervision toward expatiates are Regulation No.13 of 2003 about Empowerment, Minister of Manpower and Transmigration Regulation No.16 of 2015 about the Procedure of Expatriates Employment and Minister of Manpower and Transmigration Regulation No.35 of 2015 about the amendement of the Minister of Manpower and Transmigration No.16 of 2015 about the procedure of Expatriate Employment. The purposes of this research are to find out the effort of the Manpower and Transmigration Office of Central Java in supervising the expatriates who work in Central Java Province, to find out what documents the candidates of expatriates who will work in Indonesia must provide in accordance to the Minister of Manpower and Transmigration No.16 of 2015 and to find out what abstacles faced by the Manpower and Transmigration Office of Central Java in Supervising the expatriates in Semarang and Demak. The result of this research shows that in fact in doing supervision toward expatriates the Manpower and Transmigration Office forms a team called TIMPORA which stands for Foreign People Supervising Team. And as the leading sector is Immigration Office of Central Java. The expatriates who wants to work in Indonesia must fulfill the requirement as stated in article 36 of the Minister of Manpower and Transmigration Regulation No.16 of 2015 paragraph (1) about the Procedure of Expatriate Employment. Key Words : Employment and Supervision of Expatriate